A discounted cash-flow analysis of salmon monoculture and Integrated Multi-Trophic Aquaculture in eastern Canada. Issue 1 (2nd January 2020) - Carras, Mark A.; Knowler, Duncan; Pearce, Christopher M.; Hamer, Adrian; Chopin, Thierry; Weaire, Ted
Abstract: We assess the financial performance of an Atlantic salmon ( Salmo salar ) monoculture versus an Atlantic salmon, blue mussel ( Mytilus edulis ), and sugar kelp ( Saccharina latissima ) Integrated Multi-Trophic Aquaculture (IMTA) operation. Using updated methods and models, we improve on earlier studies of IMTA economics. A discounted cash-flow analysis was used to assess the profitability of hypothetical monoculture and IMTA operations over a 10-year period in the Bay of Fundy, New Brunswick, Canada. The IMTA operation was more profitable, even when no price premium was included for its products. A 10% price premium for IMTA salmon and mussels resulted in a substantially higher net present value for the IMTA operation than for salmon monoculture. However, uncertainty related to IMTA's financial and environmental performance, as well as IMTA's increased operational complexity, may be barriers to IMTA adoption in Canada at present. As a result, it is likely that IMTA must generate substantially greater profits than salmon monoculture to stimulate investment. Alternatively, declining salmon production in recent years may encourage IMTA adoption in the future since it can provide crop diversification and economic stability benefits. IMTA research may benefit from alternative assessment methods such as the real options approach that explicitly incorporate uncertainty.